(untitled) (Baghdad Science Journal, 2025)
The aim of this project was to study the in vitro effect of antineoplastic drugs (vincristine and vinblastine) on mice spermatozoa. Eighteen adult (age 8-9 weeks) male mice were divided into three groups equally. The animals in each group were slain by cervical dislocation, the testes were removed and two tails of epididymides isolated. Spermatozoa were obtained from the two tails of epididymides by mincing in 500 µl TCM-199.The first group non-treated (unadded) as a control group, second group added 10 µg/ml of vincristine to TCM-199 and the third group added 10 µg/ml of vinblastine to TCM-199. After 10 minutes from added of vincristine and vinblastin measured the following test: spermatozoa activity, percentage dead spermatozoa and morphological abnormalities of spermatozoa. The obtained results indicated that vincristine and vainblastine showed significant reduction in activity, while increased in percentage of dead/live spermatozoa and morphological abnormalities of spermatozoa compared with the control group. Moreover, the data showed that vincristine and vinblastin had effect on spermatozoa in vitro.